2008
DOI: 10.1093/eurheartj/ehn169
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel pre-treatment in stable angina: for all patients >6 h before elective coronary angiography or only for angiographically selected patients a few minutes before PCI? A randomized multicentre trial PRAGUE-8

Abstract: AimsTo compare two different clopidogrel regimens on the outcomes of patients undergoing elective coronary angiography (CAG)±ad hoc percutaneous coronary intervention (PCI).Methods and resultsOpen-trial randomized 1028 patients with stable angina to group A (‘non-selective’—clopidogrel 600 mg >6 h before CAG; n = 513) or group B (‘selective’—clopidogrel 600 mg in the cath-lab after CAG, only in case of PCI; n = 515). Combined primary endpoint was death/periprocedural myocardial infarction (MI)/stroke/re-interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 30 publications
2
70
0
4
Order By: Relevance
“…However, this benefit was driven mainly by periprocedural myocardial infarction, a controversial end point. Of importance, similar trends were observed in elective PCI in that 15% to 40% of NSTE-ACS patients were stabilized [27][28][29] ( Figure 2B). One may argue that the lack of mortality benefit in this patient subset is a concern.…”
supporting
confidence: 73%
“…However, this benefit was driven mainly by periprocedural myocardial infarction, a controversial end point. Of importance, similar trends were observed in elective PCI in that 15% to 40% of NSTE-ACS patients were stabilized [27][28][29] ( Figure 2B). One may argue that the lack of mortality benefit in this patient subset is a concern.…”
supporting
confidence: 73%
“…На основании нескольких рандомизированных исследований и данного мета-анализа (и в отличие от диффузной общепринятой практики), пациенты с СИБС, которым проводят диагностическую коронарную ангиографию с воз-можным проведением ЧКВ по ситуации (реваскуля-ризация в рамках одной и той же процедуры) не должны получать клопидогрел до того, как будет изучена анатомия коронарного русла [386][387][388]. Риск кровотечения при рутинной ДАТ, назначенной перед катетеризацией у пациентов, не нуждающихся в стен-тировании (нет значимой ИБС, либо ИБС, требую-щая проведения КШ), не уравновешивается обнару-живаемой пользой с точки зрения ишемических событий у лиц, проходящих ЧКВ.…”
Section: Iib B 373-375unclassified
“…Similarly, the PRAGUE-8 and ARMYDA-5 PRELOAD trials reported no differences in outcomes when clopidogrel 600 mg was given to patients with stable angina or NSTE-ACS either before (mean of 19 and 6 hours respectively) or immediately after diagnostic coronary angiography, but prior to PCI (49)(50).…”
Section: Clopidogrelmentioning
confidence: 99%